Anesthesiologist and COVID-19-current perspective - Subodh Kumar; Sanjeev Palta; Richa Saroa; Sukanya Mitra (Wolters Kluwer Medknow Publications, 2020)
In the current situation when the world is grappling with COVID-19 that has taken a toll on humanity and is continuing to affect multiples of health-care workers all over the world in vast numbers, the pandemonium (mayhem) has led to grim concerns. We have made an effort to compile and present a review that provides an insight into the management of patients for the front-line anesthesiologists of the medical war, which is being fought to curb and contain this COVID-19 pandemic. We have tried to incorporate the operating room locations, as well as the remote locations where anesthesiologist may be called upon for providing their services. Needless to say, it is of utmost importance to ensure the safety of the patient, as well as of the anesthesiologist who are involved in the patient care at this crucial juncture. The present article provides valuable information to anesthesiologists regarding handling the current pandemic in a protocolized and evidence-based manner.